PHYSICOCHEMICAL PROPERTIES OF A FUNCTIONAL SAUCE FOR FISH CANNED PRODUCTS - Toshboyeva, Samara; Dadamirzayev, Muzaffar (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
This article presents an analysis of the organoleptic and physicochemical properties of sauce–paste semi-finished products developed for fish canned products. The study focuses on current and highly relevant issues related to meeting the growing consumer demand for meat products, which are among the most widely consumed natural food products today. Particular emphasis is placed on expanding the assortment of natural and affordable products, as well as on the development of new and high-quality product types. In this context, the results of research aimed at improving the quality and functional characteristics of sauces intended for fish canning are highlighted.